MORPHOLOGICAL CHANGES IN REGIONAL LYMPH NODES IN ALCOHOLIC PANCREATITIS - Y.A. Musayeva; A.E. Latibjonov (Journal of modern medicine, 2026)
During the study of morphological changes in the regional lymph nodes of the pancreas in alcoholic pancreatitis, the following were studied. In particular, the development of subcapsular edema in the lymph nodes, the presence of varying sizes of lymphoid follicles in the cortical areas from morphofunctionally active areas, the absence of reactive foci in germinal centers, the exposure of paracortical areas, the formation of cystic cavities around the brain bands in the medullary layer, primarily an increase in reticulocytes, histiocytes, fibroblasts, and macrophages, a decrease in the variable mixture of T and B lymphocytes, and changes in the form of exposure and fullness around postcapillary venules were identified.